Patient-Reported Outcomes for Fractures of the Acetabulum: A Comparison Between Patient-Reported Outcomes Information System and Traditional Instruments. Issue 2 (15th January 2022) - Schumaier, Adam P.; Matar, Robert N.; Ramalingam, Wendy G.; Archdeacon, Michael T.
Abstract : Introduction: The objective of this study was to compare instruments from the Patient-Reported Outcomes Information System (PROMIS) with previously validated acetabulum fracture outcome instruments. Methods: This study included adult patients presenting for routine follow-up at least 3 months after surgical treatment of an acetabulum fracture. Participants completed four different patient-reported outcomes in a randomized order: PROMIS Mobility, PROMIS Physical Function, Short Form 36 (SF-36), and Short Musculoskeletal Functional Assessment (SMFA). Primary outcomes were the correlations between instruments, floor/ceiling effects, and survey completion time. The effects of age, education, and race on survey completion time were also evaluated. Results: Overall strong correlations were observed between PROMIS instruments and the SMFA/SF-36 (r = 0.73 to 0.86, P < 0.05) with weaker, more moderate correlations in those with >18 months of follow-up (r = 0.41 to 0.76, P < 0.05). No instruments demonstrated notable floor or ceiling effects. The PROMIS outcomes required less time to complete (PROMIS [56 to 59 seconds] than SF-36 [5 minutes 22 seconds] and SMFA [6 minutes 35 seconds]; P < 0.001). Older individuals required more time to complete the PROMIS PF (0.5 s/yr, P = 0.03), SF-36 (2.35 s/yr, P = 0.01), and SMFA (3.85 s/yr, P < 0.01). Level of education did not affect completion time; however, African Americans took significantly longer than Caucasians to complete the SMFA and SF-36 by 151 and 164 seconds ( P < 0.01). Conclusion: This study supports that the PROMIS Mobility and Physical Function surveys are much more efficient instruments for evaluating patients with acetabulum fractures when compared with the SMFA and SF-36. Convergent validity of the PROMIS instruments was overall strong but weaker and more moderate in those with a long-term follow-up, and additional study is suggested for longer-term outcomes. Level of education did not influence survey completion time; however, it took markedly longer time for older individuals and African Americans to complete the SMFA and SF-36.